PEMBINAAN EKSTRAKURIKULER OLAHRAGA DI SEKOLAH DASAR ISLAM AL-AZHAR 14 SEMARANG TAHUN AJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
Background Issues about Sport extracurricular development of Elementary School (SD) Al-Azhar 14Semarang got some feats as the result of sport extracurricular development. Sport extracurricular developmentneeds an organisation , development pattern, exercise program and instrument. The research focus of this caseis "how the sport extracurricular developing in Elementary School (SD) Al-Azhar 14 Semarang is" Thepurpose of this research is to know about the sport extracurricular developing in Elementary School (SD) Al-Azhar 14 Semarang. This research uses descriptive qualitative research approach, it means that the procedureor the manner of how to resolve this case is by exposing the studied object (person, organisation, society, ets)based on the actual facts at present. The collection of data use an interview, observation and documentationmethods. While the data analizing method that is used in this case is triangulation technique.Analysis of thedata by data reduction, data display and verivication/concution drawing. The results of this research are asfollows : (1) The condition of Sport extracurricular development of Elementary School (SD) Al-Azhar 14Semarang has an organitation, or management of Sport extracurricular which is well held accordance with itsduty. (2) The exercise program for the sport extracurricular is good. (3) It Has a good coach who has a goodability in bascetball, taekwondo and football. (4) It has good instruments enough, equipments and tools.